Phan Chau Trinh and His Political Writings - Phan, Chu Trinh, 1872-1926 (Book collections on Project MUSE., 2009)
Phan Chau Trinh (1872-1926) was the earliest proponent of democracy and popular rights in Vietnam. Throughout his life, he favored a moderate approach to political change and advised the country's leaders to seek gradual progress for Vietnam within the French colonial system. Unlike many of his contemporaries, he did not favor anti-French military alliances or insurgent military resistance, arguing that "to depend on foreign help is foolish and to resort to violence is self-destructive." As a result of his exposure to Chinese reformist literature, Phan Chau Trinh assigned top priority to promoting democracy and human rights and to improving Vietnamese people's lives. He believed that true independence could only be achieved by changing the Vietnamese political culture, and he articulated penetrating criticism of the corruption and superficiality of Vietnam's officials. His emphasis on changing the fundamental values governing the ruling class's behavior, as well as his skepticism regarding anticolonial resistance, set Phan Chau Trinh apart from his contemporaries and mark him as a true revolutionary. Vinh Sinh's masterly introduction to Phan Chau Trinh's essays illuminate both this turbulent era and the courageous intelligence of the author